(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the importance, capabilities, and possible future changes of artificial intelligence in the education system. The issues of personalizing the educational process with the help of artificial intelligence, improving curricula, introducing virtual assistants, and expanding the possibilities of distance learning are discussed. It also highlights the role of artificial intelligence in democratizing global education, training teachers, and providing solutions to problems related to ethical aspects of education. The article examines in detail the ways to increase the effectiveness of education through the use of artificial intelligence in education and its social significance. In addition, it discusses the advantages of using artificial intelligence in education, its positive impact on the quality of education, its ability to organize the educational process with its help, and the creation of many conveniences in the educational process.